Modelo de referência para processo de exportação de produtos alimentícios para União Europeia - Franzosi, Lígia de Oliveira (2016)
Many studies highlight the importance of growth in world trade for encouraging the economic advancement of nations as a globalization motivator. Export is one of the best ways for a company to leverage its growth, and one of the sectors that most stands out in exports is the agrobusiness. However, companies that export more easily are the large ones, it has support and knowledge of the procedures involved. The small companies have difficulties due to the high cost involved, the lack of training and mastery of the procedures involved, particularly when faced with demanding countries, which are potential buyers. The European Union countries are among the largest importers of food products from Brazil, however, it is those with the highest demands on import products. Therefore the objective of this study is to develop a reference model that considers the technical and regulatory requirements in Europe to help small industry in food export process. For this is presented a review of internationalization of companies, requirements of the export process and difficulties encountered during the export process. Then, a field research is presented in order to identify the difficulties found by the food industry during the export process. It also examines some of the main existing models to support the export process, which are analyzed and compared in order to obtain the best practices of each of them, according to the European requirements. With the collection previously held, draws up a model to support a complete export process, from compliance with national requirements, to the international requirements in various areas. The model is subjected to evaluation of their concept by experts who offer suggestions for improvements to the model presents better performance in the industrial field.